A hot topic – heat waves and stroke. Issue 7 (October 2014) - Chan, Fiona; Francis, Oliver; Dodd, Lizzie; Mahdi, Zain; Koblar, Simon A.
<x xml:space="preserve">Abstract</x> Following a heat wave in January 2014 in Adelaide, state capital of South Australia, we asked the question whether extreme heat was associated with an increase in stroke incidence. We found in the literature that the association between stroke presentation to hospital and meteorological factors has long been a topic of debate and subject to numerous studies. The literature indicated that an association between heat waves and an increase in admissions for stroke was unlikely in Australia and the United States. We suggest that it may be inappropriate to generalize this conclusion to other countries and rural areas. In view of the global climate change debate, we suggest that prospective studies be focused in developing countries and rural areas to assess the real impact of extreme heat on respective populations to better inform stroke physicians and health policy makers.